Ardisia assamica sp. nov. (Primulaceae—Myrsinoideae) from Assam, India - Baruah, Manash; Saikia, Gitartha; Devi, Nilakshee (Phytotaxa, 2025)
A new species of Ardisia (Primulaceae), A. assamica is proposed based on material collected from Assam, India. It is characterized by compound cyme inflorescence; triangular sepals with ciliate margins bearing golden-yellow hairs; imbricate petals and non-pentahedral fruits. Detailed morphological description, colour photographs, phenology and distribution records are provided. A comparative analysis with two closely related species A. quinquegona Blume and A. quinquangularis A. DC. is also presented highlighting distinguishing characters.